EPCT-08. ACTIVITY OF LAROTRECTINIB IN PEDIATRIC TROPOMYOSIN RECEPTOR KINASE (TRK) FUSION CANCER PATIENTS WITH PRIMARY CENTRAL NERVOUS SYSTEM (CNS) TUMORS. (4th December 2020) - Goto, Hiroaki; Geoerger, Birgit; DuBois, Steven G; Grilley-Olson, Juneko E; van Tilburg, Cornelis M; Schulte, Johannes; Kang, Hyoung Jin; Tahara, Makoto; Boni, Valentina; Perreault, Sebastien; Capra, Michael; Reeves, John A; et al.
Abstract: BACKGROUND: TRK fusions are oncogenic drivers in a variety of tumors, many involving the CNS. Larotrectinib, a selective FDA- and EMA-approved TRK inhibitor, demonstrated a 79% objective response rate (ORR) and a 35.2-month median duration of response (DoR) in adult and pediatric patients with various non-CNS solid tumors harboring NTRK gene fusions. We report the clinical activity of larotrectinib in pediatric patients with primary TRK fusion CNS tumors. METHODS: Patients aged <18 years with primary CNS tumors harboring an NTRK gene fusion detected by local molecular testing who were treated with larotrectinib in two clinical trials (NCT02637687, NCT02576431) were identified. Larotrectinib was administered until disease progression, withdrawal, or unacceptable toxicity. Disease status was investigator assessed (RANO). RESULTS: As of February 2019, 14 pediatric patients with primary TRK fusion CNS tumors were identified. Gene fusions involved NTRK2 (n=10), NTRK1 (n=2), and NTRK3 (n=2). Median age was 7.0 years (range 1.3–16.7). ORR was 45% (95% CI 17–77%) among 11 evaluable patients. Two patients had complete responses (pending confirmation), three had confirmed partial responses, and six had stable disease. 24-week disease control rate was 73%. DoR ranged from 2.6+ to 5.5+ months and progression-free survival ranged from 0.03+ to 13.9+ months. Duration of treatment ranged from 0.03+ to 16.6+ months. Treatment-emergent adverse events were mainly grade 1–2. CONCLUSIONS: Larotrectinib resulted in objective responses and durable disease control in pediatric patients with primary TRK fusion CNS tumors. These results support expanded testing for NTRK gene fusions in patients with CNS tumors.